Thermal decomposition kinetics of melt-mixed ethylene-co-vinyl acetate – based bio-composites. (August 2021) - Stephy, A.; Antony, A.M.; Francis, T.
Abstract: Bio-composites of ethylene-co-vinyl acetate (EVA) with chitosan (CS) and chitosan-g-PANi (CS-PANi) have been developed by using a melt-mixing process by varying the composition of fillers. Investigations on the degradation mechanism of thermoplastics lead to insights of their performance at high temperatures. The decomposition kinetics of the bio-composites was determined by plotting thermograms at different heating rates. The model-free Flynn-Wall-Ozawa and Kissinger method has been used to estimate the energy of activation (Ea ) of the developed composites. The activation energies of EVA/CS composites lie between 162 and 209 kJ/mol and EVA/chitosan-g-PANi composites within the range of 145–256 kJ/mol. The variation in activation energy across the extent of conversion levels denotes multistep kinetics of degradation. The calculated Ea has been found to be in good agreement with the literature reports. Graphical abstract: Image 1 Highlights: Melt-mixed bio-composites of ethylene-co-vinyl acetate with chitosan (CS) and CS-g-PANi (CS-PANi) as fillers have been developed. The decomposition kinetics of the bio-composites were determined using model-free methods, namely, Flynn-Wall-Ozawa and Kissinger. The activation energies of EVA/CS (CE) composites lie between 162–209 kJ/mol and EVA/CS-g-PANi (EPCS) composites within the range of 145–256 kJ/mol. The calculated Ea denotes multistep kinetics of degradation for the prepared composites. Compared with pure EVA, the Ea values of the composites show an increased thermal resistance, making the composites compatible for flame retardant applications.